Status Kesehatan Pasar Ditinjau Dari Aspek Lokasi Dan Bangunan Pada Pasar Ciputat Dan Pasar Modern BSD Kota Tangerang Selatan - Rusman Efendi; Jihan Nada Alya Syifa (HB PRESS, 2018)
The market can be a major pathway in the spread of some diseases like diarrhea that goes into the body through contaminated food or drink pathogenic bacteria, the SARS (Severe Acute Respiratory Syndrome) and even Bird Flu (Avian Influenza). One way to break the spread of the disease that can occur in a market environment that is need for the implementation of a good market environment sanitation in accordance with the guidelines of the healthy market Kepmenkes Number 519/Menkes/SK/VI/2008. The purpose of this research is to know the health status of the market review of aspects of the location and the building of the Modern Market and Ciputat Market BSD. This research was conducted in may 2018. This research is the kind of research kuantitif with a descriptive observational approach by using a cross sectional study design, which is based on checklist No. 519 Kemenkes the year 2008 about the market Healthy. Health status of Ciputat Market aspect of the site is categorized both by a score of 80% or 400, but in the aspect of market building Ciputat categorized unfavourable 845 or 43.4% while the BSD Market Health Status review of the aspects of the site categorized both by a score of 500 or 100% but in aspects of the property market are categorized either by BSD score 1692 or 86.8%. Health status of both the market and the market of ciputat market both BSD reviewed aspects of the location's been good, for health status review of aspects of the market building BSD has also good but the market building aspects of ciputat. advice for market managers to devise a healthy market building, and who have both enhanced good facilities and infrastructure so as to create a healthy market